Comparative Study of N-Butyl-2-Cyanoacrylate and Indirect Reduction for Management of Comminuted Fracture - Ajay Nayakawadi; Lishoy W. Rodrigues; Nishant Gaonkar; Ajay Kumar Dogra; C. V. Mahajan; Yadavalli Guruprasad (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Various studies in the past have shown that the butyl cyanoacrylate (CA) chemical group has shown the best results in terms of toleration by tissues. Aim: To compare and evaluate the efficacy of N-butyl-2-CA and IR with no fixation in the management of CF of AWMS. Material and Method: A total of 26 samples were included in our study to understand clinically and radiographically CAWFMS with two different groups, that is, A as control and B as test with different follow-ups. Result: With regard to clinical aspect, for pain, the difference between groups was nonsignificant at 1 month and 3 months while significant for 1 week. For swelling and FBR, the difference was nonsignificant for all the follow-ups. With regard to radiographical aspect, ARSF, the difference was nonsignificant immediately but significant after 3 months, and at SP, the difference was significant at both immediate and 3 month follow-ups. Conclusion: Our study was in favor of the use of N-butyl-CAG for management of AWMS in patients with ZMC fractures due to its biocompatibility and effectiveness during the treatment.